The impact of commercial bank’s characteristics on micro, small, and medium enterprises in India - Motiniva Nayak (Universitas Islam Indonesia, 2017)
The paper discusses the changes in the credit distribution to the micro, small and medium enterprises (MSME) sector. It analyses the relationship between commercial banking characteristics and its credit to the sector. It builds an econometric analysis on the relationship between share of credit to MSE and banking characteristics, namely the size, performance of bank, non-performing asset (NPA) out of MSME lending, and capital to risk weighted ratio (CRAR). It finds a negative relationship between the size of the bank and proportion of credit flows to the sector. It also finds that better performing banks are not interested in lending to the sector.